TRANSFORMASI PERILAKU KEAGAMAAN DI ERA MEDIA BARU 4.0 - Nurhasanah (AT-TANZIR: JURNAL ILMIAH PRODI KOMUNIKASI PENYIARAN ISLAM, 2021)
This study aims to find out how the transformation of religious behavior in the new media era 4.0 and what efforts are made to overcome the transformation of religious behavior in strengthening religious moderation in the new media era 4.0. The research method uses literature study by collecting data from documentation using descriptive-analytical method. types of library data collection methods (Library Research). The method that the author uses is a study by studying and browsing the literature relating to the subject being studied in the form of books, articles, websites and other writings containing information and related data using titles. The results of the study indicate that the transformation of religious attitudes is experiencing turbulence in the flow of the industrial revolution. This changing perspective on creating or managing this industry also has an impact on the way people understand beliefs, express, and communicate to others. People who respond to the behavioral phenomena presented by the media in this 4.0 era, provide changes in attitude and behavior in their use as a result of which religious values ​​begin to change (transformation). Efforts were made to strengthen religious education among citizens in the face of changes in people's attitudes in this 4.0 era. Islam thinks of appropriate efforts in dealing with these behavioral changes. In this correlation, trust education functions as an effort to foster religious and spiritual people who are able to adapt to face Era 4.0.